1991
DOI: 10.1182/blood.v78.2.451.451
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of a new human leukemia cell line derived from M4E0

Abstract: A new human leukemia cell line, designated as ME-1, was established from the peripheral blood leukemia cells of a patient with acute myelomonocytic leukemia with eosinophilia (M4E0). This cell line has the characteristic chromosome abnormality of M4E0, inv(16) (p13q22). When cultured in RPMI 1640 medium containing 10% fetal calf serum, ME-1 cells were monoblastoid, but with the addition of cytokines such as interleukin-3 (IL-3), granulocyte-macrophage colony-stimulating factor (GM-CSF), IL-4, or medium conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Because HDAC1 colocalizes with RUNX1 and CBFb-SMMHC on gene promoters, it is possible that HDAC1 is part of the RUNX1:CBFb-SMMHC complex. Before testing this, we confirmed that HDAC1 is expressed in leukemia cells from knockin mice with a conditional Cbfb-MYH11 allele (Cbfb þ/56M ) under the control of the Mx1-Cre Recombinase (Mx1-Cre þ ) transgene, (hereafter CM þ cells) and in the human inv(16) cell line, ME-1 (14,15,23,31). We detected increased levels of HDAC1 in three different CM þ mouse samples as compared with bone marrow from wild-type mice.…”
Section: Hdac1 Is a Member Of The Cbfb-smmhc:runx1 Complexmentioning
confidence: 84%
“…Because HDAC1 colocalizes with RUNX1 and CBFb-SMMHC on gene promoters, it is possible that HDAC1 is part of the RUNX1:CBFb-SMMHC complex. Before testing this, we confirmed that HDAC1 is expressed in leukemia cells from knockin mice with a conditional Cbfb-MYH11 allele (Cbfb þ/56M ) under the control of the Mx1-Cre Recombinase (Mx1-Cre þ ) transgene, (hereafter CM þ cells) and in the human inv(16) cell line, ME-1 (14,15,23,31). We detected increased levels of HDAC1 in three different CM þ mouse samples as compared with bone marrow from wild-type mice.…”
Section: Hdac1 Is a Member Of The Cbfb-smmhc:runx1 Complexmentioning
confidence: 84%
“…Patient 2 was a 65-year-old man with a clinical diagnosis of AML-MlEo. Patient 3 had AML-M~Eo, whereas patient 4 had CML in blast crisis associated with eosinophilia (Yanagisawa et al, 1991;Evers et al, 1992). Patient 6 was a 34-year-old woman with a clinical diagnosis of AML-M4 without elevated eosinophil count.…”
Section: Patient Descriptionmentioning
confidence: 99%
“…Bone marrow samples were collected from all patients except patient 3. A cell line has been developed from patient 3 cells (Yanagisawa et al, 1991), and cultured cells were harvested for analysis.…”
Section: Patient Descriptionmentioning
confidence: 99%
“…To further explore the detailed functional pathways induced by CBFβ-MYH11 alone, we generated a stable dox-inducible CBFβ-MYH11 knockdown (KD) cell line based on the inv(16) cell line ME-1 25 (Figure 4A), and further examined genome-wide changes in the transcriptome as well as the acetylome. Previously, CBFβ-MYH11 transduction of CD34 + cells was shown to enhance proliferation 26 .…”
Section: Resultsmentioning
confidence: 99%